The Role of Parents in Preventing Teenage Pregnancy in Rural Areas of Banyumas District - Kurniawan, Arif; Gamelia, Elviera (YCAB Publisher, 2024)
Background:One of the factors contributing to Indonesia's high maternal mortality rate is the high incidence of teenage pregnancy in Banyumas. The family, particularly parents, plays a crucial role in influencing teenage pregnancy, as they are expected to act as educators, motivators, supervisors, communicators, and counselors for their teenagers. Objective:The purpose of this study was to identify the factors that influence the role of parents in the prevention of teenage pregnancy. Methods:A cross-sectional study design was employed, focusing on female participants. A cluster random sampling technique was used to obtain a sample size of 150 parents from the study population, using the proportion estimation formula. The validity and reliability of the questionnaire used were tested. Data were analyzed using logistic regression. Results:The univariate analysis revealed that 93.2% of respondents were female, 25.3% were aged between 38 and 42, 61.3% had only completed elementary school, 63.3% were housewives, 58% had incomes below IDR 1.350.000, 52% had monthly family expenses under IDR 1.350.000, and 42.7% had five or more dependents. The bivariate chi-square test showed an association between parental resources, the role of health professionals, knowledge, attitudes, and societal values in the prevention of teenage pregnancy. The multivariate analysis using logistic regression indicated that the value of people and resources significantly impacts the role of parents in this regard. Conclusion:The role of parents in preventing teenage pregnancy is influenced by the value placed on people and resources. Keywords: Maternal mortality; adolescent pregnancy; role of parents; knowledge; attitudes